Remote sensing data for monitoring and evaluating burned areas: the case of Emas National Park in Brazil - Shimabukuro, Yosio Edemir; dos Santos, João Roberto; Lee, David Chung Liang; Pereira, Marcos da Costa (Pesquisa Agropecuaria Brasileira, 1991)
In the process of implantation and management of cattle raising and agricultural activities in Brazil, burning of vegetation cover is a commonly employed procedure, for example, in the Central-West part, occupied by savannas. However, fire action has frequently reached the environmental protection areas such as the Emas National Park (Goiás State), which may cause destruction of the habitat and niche, death of smaller animals, besides the environmental polution. The objective of this work is an analysis of TM/Landsat and AVHRR/NOAA digital data as a tool for evaluating and monitoring the areas damaged by fire in this National Park. Based on TM images (July 29, 1988 and August 14, 1988) and AVHRR data obtained during this period, a monitoring of fire action and the distribution analysis of the burned area related to the vegetation type were made. Change detection techniques such as post-classification comparison and principal components analysis were utilized for TM images. The results show an estimate of 73,884 hectares of burned vegetation areas. The integration of TM (high spatial resolution) and AVHRR (high temporal resolution) data permits to monitorate the burning process, i.e., from the active fires detection to the burned area estimation.